Strategi Pengembangan Bisnis Peternakan Ayam Kampung ChikenBall - Iqbal Faui (CV. ITTC INDONESIA, 2024)
The implemented strategy for developing the laying hen business has been shown to significantly increase sales turnover in the Chikenball free-range chicken farming business. This strategy must be supported by a pricing policy for the product, ensuring that production factors are met effectively. Based on the SWOT matrix analysis, the business development strategy implemented by the Chikenball free-range chicken farm includes: Strengths: Maintaining and improving service to maintain customer loyalty by providing a friendly and courteous attitude. Maintaining quality, quantity, and economic stability, and increasing production volume. Weaknesses: Increasing product marketing through promotions and coordinating with entrepreneurs involved in developing the market for Chikenball free-range chicken farming products. Organizing and participating in training to broaden knowledge in business development. Opportunity Strategy: Improving and maintaining the marketing process in terms of product, pricing, distribution, and promotion.